How redistributive policies reduce market inequality: Education premiums in 22 OECD countries - David Weisstanner; Klaus Armingeon (Luxembourg Income Study (LIS), 2018)
What explains the large cross-country variation in the wage premium for higher education? Economic analyses of wage differentials by education point to technological change and globalisation, but we know little about the impact of different types of public policies. We argue that public education spending and tax-transfer policies contain the spread of 'education premiums' through material incentives (decommodification) and attitudinal responses, i.e. changing attitudes towards education premiums and the motivation to request a maximum return on individual investment in education. The empirical analysis relies on a new dataset of education premiums constructed from Luxembourg Income Study microdata, covering 22 OECD countries between 1989 and 2014. We provide evidence that taxation levels and public education spending particularly affect education premium levels and changes within countries. For the literature on income inequality, these findings imply the need to pay attention more systematically to redistributive policies shaping the 'market' distribution of incomes.
Keywords: I24; I26; I38; 330; wages; inequality; education; public policy; redistribution